Harmonic Centrality and Centralization of the Bow-Tie Product of Graphs - Ortega, Jose Mari E.; Eballe, Rolito G. (Communications in Mathematics and Applications, 2023)
The bow-tie product is a newly named binary operation on graphs. In this article, we present some properties of the bow-tie product of graphs, as well as some results on both the harmonic centrality and the harmonic centralization of the bow-tie product of the path \(P_2\) with any of the path \(P_m\), cycle \(C_m\), star \(S_m\), fan \(F_m\), and wheel \(W_m\).
Keywords: Bow-tie product; Harmonic centrality; Harmonic centralization